Molybdenum disulfide saturable absorber for eye-safe mode-locked fiber laser generation - Latiff, Anas Abdul; Cheng, Xiau San; Rusdi, Muhammad Farid Mohd; Paul, Mukul Chandra; Harun, Sulaiman Wadi; Ahmad, Harith (World Scientific Publishing, 2018)
We demonstrated an all-fiber mode-locked Thulium-Holmium co-doped fiber laser (THDFL) based on molybdenum disulfide (MoS2) tape saturable absorber. The THDFL generates a mode-locked pulse in anomalous regime at 1,979nm using 5m long Thulium-Holmium co-doped (THDF) as a gain medium. Through mechanical exfoliation method, the MoS2 was mechanically extracted from a commercial MoS2 crystal by using a clear scotch tape. Through balanced twin-detector measurement, the obtained MoS2 tape has a nonlinear absorption of 10% with 100MW/cm2 saturation intensity. Under 775mW to 852mW pump power, a stable pulse train was obtained at 9.12MHz repetition rate with a signal-to-noise ratio (SNR) of 45dB. The maximum output power and pulse energy were measured about 20mW and 2.2nJ, respectively. With a 3-dB spectral bandwidth of 2.1nm, the minimum possible pulse width was determined as 1.97ps.